PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA NILAI PERUSAHAAN - Umbara, Dewa Made Bagus; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
This study aims to determine the effect of CSR on corporate value. This research was conducted in the IDX, with a population of 407 companies. This study uses regression analysis techniques. Based on the analysis it was found that (1) CSR (Corporate Social Responsibility) has a positive effect on the value of the corporate; (2) the positive impact of CSR disclosure on the value of the corporate is categorized as a high-profile corporate; (3) the positive impact of CSR disclosure on the value of the corporate is categorized as a low profile corporate.
Keywords: NP, CSR, profile